CUSTOMER INFORMATIONSYSTEM DELIVERY OF GOODS IN TRASPATINDO ABADI SEJAHTERA COMPANY - Tinawati Tinawati; Aqwam Rosadi Kardian, SKom, MM (Jurnal Sistem Informasi, 2002)
In the business world, especially service delivery, accuracy of delivery of customer shipments are absolutely necessary. PT. Transpatindo Abadi Sejahtera (TAS Express) itself is a national private company engaged in shipping services or international courier services that use air transport as a means of freight transportation. As a company which is engaged in service delivery, service is key in keeping customers. Companies are required to provide information and excellent service, fast and accurate. on this occasion the author wants to analyze how the system is running on the customer service in an effort to improve the quality of service to customers.